(untitled) (Baltic Journal of Sport and Health Sciences, 2019)
Background. Aikido is a philosophy and an Eastern martial-art which is conjectured to have many positive effects on mind and body. At this time there is limited, but growing research on this topic. The objective of the current work was to examine for the first time the hypothesis that aikido training, like many other western forms of organized physical activities, has acute psychological benefits as manifested via favourable changes in affect and the flow experience. Methods. Aikidokas (N = 53) took part in an in-situ investigation in which they completed the Positive Affect Negative Affect Schedule (PANAS) on at least three different occasions before and after their practice. They also completed a flow questionnaire at least on three occasions after their practice. Results. The results indicated that positive affect increased, and negative affect decreased (p < .001) from pre- to post-practice. Aikidokas reported flow experience that on the average was not greater than that reported for other exercises; however it was greater than that reported after video-sport games. The reported flow was independent of the magnitude of change in positive and/or negative affect. The more experienced aikidokas experienced greater skill-challenge harmony, but not oneness with the experience, which are two constructs in flow, than less experienced practitioners. Conclusion. These findings reveal relatively clearly for the very first time in the literature that aikido practice has acute, or immediate, psychological benefits akin to other martial arts and exercises.